Eficiência de fungos entomopatogênicos sobre formigas cortadeiras (Hymenoptera: Formicidae) - Bezerra, Nathalia Souza (2018)
Leaf-cutting ants of the genera Atta and Acromyrmex are recognised as important pests of the Neotropics. Currently, the main control method is the use of chemical insecticides. However, there is a growing concern about the negative effects of the frequent applications of insecticides on non-target organisms, human health and the environment. Entomopathogenic fungi can naturally infect insect hosts via direct penetration of the cuticle and have been investigated worldwide as promising biological control agents. Thus, the aim of this study is to evaluate the efficiency of Beauveria bassiana, Beauveria brongniartii, Metarhizium anisopliae var. anisopliae, Paecilomyces sp. and Aspergillus sp. against leaf-cutting ants in laboratory. We also analyzed the effect of Fipronil on the vegetative growth and conidiogenesis of the fungal isolates. For each species of fungus, an experiment with 90 specimens of leaf-cutting ants was carried out, corresponding to three replicates of 10 ants for each treatment (Treatment 1Control group = autoclaved distilled water + Tween 80 0.01 %; Treatment 2 = suspension of 1.0 x 104 conidia.mL-1 + Tween 80 0.01 %; Treatment 3 = suspension of 1.0 x 108 conidia.mL-1 + Tween 80 0.01 %). The ants were transferred individually to Petri dishes containing filter paper with 1 mL of the conidia suspension and cotton balls moistened with a 10 % honey solution. The plates were kept at a temperature of 25 ± 2 °C and relative humidity of 70 ± 10 %, and evaluated every 24 hours for 10 days, to observe the extrusion of the fungi and to confirm the death of the insects by the pathogens. To determine the effect of the insecticide on the vegetative growth and conidiogenesis of the fungal isolates, 0.8 g/L of the product and 0.3 g/L of penicillin were added to the SabouraudDextrose-Agar culture medium. After 10 days, each colony diameter was measured with a ruler and the conidia were counted using a Neubauer chamber. As a result of the bioassay, both concentrations of conidia used (1.0 x 104 and 1.0 x 108 conidia.mL-1) were able to assure infection and disease progression in the leaf-cutting ants, with the mortality of the ants ranging from 4.80 ± 2.10 to 9.99 ± 0.00 (mean ± SE) and LT50 ranging from 6.01 to 10.22 days. Regarding the two concentrations tested, we observed that, in some cases, insect mortality increased as conidia concentration increased. Among all isolates Aspergillus sp. was the one that had the highest mean mortalities (9.99 ± 0.10 and 9.99 ± 0.00) and the lowest LT50 (6.47 and 6.01 days) for both concentrations. Fipronil-treated fungal isolates showed a reduction in vegetative growth, but the insecticide did not significantly compromise the conidiogenesis of the isolates. In conclusion, the bioassay described in this study allowed the discovery of isolates with great potential to be evaluated in field conditions for the biological control of leaf-cutting ants, contributing to the development of more effective and environmentally friendly alternatives for the control of these insect-pests and Fipronil, was classified as “compatible” with the fungal isolates based on the in vitro compatibility test.